Buried in Treasures : Help for Compulsive Acquiring, Saving, and Hoarding. - Tolin, David F. (Oxford University Press, USA, 2007)
1. How to use this Book 2. What is Compulsive Hoarding? 3. How did this Happen? 4. Meet the Bad Guys 5. Meet the Good Guys: Cognitive-Behavioral Strategies for Beating Hoarding 6. Enhancing Motivation 7. Sorting/Discarding: Getting Ready 8. Sorting/Discarding: Let's Go! 9. Help with Reducing Acquiring 10. Here come the bad guys: Part 1. Motivation and Working Time 11. Here come the bad guys: Part 2. Motivation and taking on the brain 12. Maintaining your Gains.